Performance and Emission Characteristics of Diesel Engine Using Ether Additives: A Review - Quoc Bao Doan; Xuan Phuong Nguyen; Van Viet Pham; Thi Minh Hao Dong; Minh Tuan Pham; Tan Sang Le (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Pressure on alternative fuels and strict environmental regulations are driving a strategic shift in the efficient use of renewable biofuels. One of the promising biofuel candidates recently interested by scholars is a biological or organic additive that is added into diesel or biodiesel fuel to improve engine performance and reduce pollutant emissions. With efforts to improve efficiency and combustion quality in cylinders, combustion characteristics, flame structure and emission formation mechanism in compression ignition (CI) engines using blended fuel with organic additives have been studied on the effect of additive properties on the combustion behaviour. In this review, the physicochemical properties of typical organic additives such as ethers compounds and their effects on engine performance and emission characteristics have been discussed and evaluated based on conclusions of recent relevant literature. The results of the analysis revealed the prospect of using ether additives to improve combustion in cylinders and reduce pollutant emissions from CI engines. Obviously, the presence of higher oxygen content, lower viscosity and density, and higher cetane number resulted in a positive change in the combustion dynamics as well as a chain of mechanisms for the formation of pollutant precursors in the cylinder. Therefore, ether additives have a significant contribution to the sustainable energy strategy of the transportation sector in the next period when internal combustion engines still dominate in the competition for energy system choices equipped on vehicles.